«COALITION OF THE WILLING»: A NEW ARCHITECTURE OF SECURITY AND GUARANTEES FOR UKRAINE - Moiseieva, Tetiana (Current Problems of Sustainable Development, 2026)
The article provides a comprehensive analysis of the «Coalition of the Willing» as a new mechanism for European security in the context of the transformation of the modern system of international relations and the ongoing Russian-Ukrainian war. The prerequisites for the formation of the coalition, its political and security goals, as well as its role in creating a system of intermediate security guarantees for Ukraine in the absence of NATO membership are studied. Particular attention is paid to the analysis of the strategic tasks of the coalition, including: deterring further aggression by the Russian Federation, supporting Ukraine’s defense capabilities, developing multinational forces, and deepening military-industrial cooperation between Ukraine and European states. The legal basis for the functioning of the association is studied, in particular the Paris Declaration and the use of NATO SOFA standards as a legal foundation for the presence of foreign troops on the territory of Ukraine. Particular attention is paid to the military concept of the Multinational Force for Ukraine (MNF-U), aimed at strategically deterring aggression and protecting critical infrastructure. The positions of key international actors on the deployment of “assurance forces” are analyzed in detail. The key political, institutional and resource challenges facing the coalition are characterized, including dependence on US military support, intra-European contradictions, limited defense-industrial resources and the risks of military escalation by Russia. It is proven that adherence to the principle of “nothing about Ukraine without Ukraine” within the framework of the Coalition’s activities has ensured the transformation of the state from an object of international politics into an active subject of regional security policy and a donor of unique combat experience. It is emphasized that the “Coalition of the Willing” is gradually turning not only into a mechanism for coordinating assistance to Ukraine, but also into one of the elements of the formation of a new European security architecture.
Keywords: Coalition of the Willing; european security; security guarantees; strategic deterrence; Multinational Force – Ukraine (MNF-U); russian-ukrainian war; military-industrial integration